The Role of Public Relations (PR) as a Management Tool in the Pharmaceutical Industry - Abakli-Zakli, Dorcas Inaka (UniMAC - GIJ, 2020)
Healthcare is a field mostly faced with numerous complex organization-public relationships, and the need to manage the relationships among the various publics has increasingly become complex. The role of public relations is very important especially in sectors where communication is key to a better public outcome like the health sector. Without the right communication tool, stakeholders may not be able to understand some necessary information for their health and well-being. This paper explored the role those public relations as a management function within the health care and pharmaceutical industry. The discussion was based on a series of empirical research literature on public relations and healthcare. The paper argues that the present and future of health and pharmaceutical care is cantered on the central role of the patient looking for new ways of communicating with health providers and this is facilitated by public relations. The study shows that public relations in the pharmaceutical industry has changed in accordance with the change that has evolved in healthcare. However, it is not entirely different from public relations in other industries since the main aim is to maintain a long-term relationship between health organizations and its publics as well as manage reputation. The author suggests that it is necessary for the management of health organizations to recognize the important role that the public relations play in creating good internal and external PR and include the public relations department in all decision-making and operations in the organization
THESIS